Technical Analysis of the Masonry of the Bargello’ Palace, Florence (Italy) - Massimo Coli; Anna Livia Ciuffreda; Tessa Donigaglia (Applied Sciences, 2022)
This study defines the assemblage, materials, and mechanical parameter of the XIV century Bargello Palace at Florence (Italy). For this purpose, according to the rule in force, NDT and LDT had been performed on the Bargello walls, namely: direct observations, georadar, ultrasonic, thermic, DAC-test, and endoscopy. The results outline that the Bargello masonries are well done, as use in Florence in the XIV–XV centuries; they are solid walls, made in tightly sealed flat quoins, with external facing and internal plastering, and with a percentage of stones to mortar equal to about 70%. The results allow assigning of the Bargello’s masonry to one of the categories provided by the rules in force, with the relative mechanical parameter values for the need of a seismic verification assessment.